Factors influencing internship satisfaction and their relationship to self-perceived competence among hospitality undergraduates of public universities in Malaysia - Ruslan, Syafinaz (2021)
Most of the local universities integrate internship programs in their curriculum design, which intends to enhance students' skills and promote the real work environment. The internship program benefits the students by giving opportunities to polish their career skills and to gain on-the-job experiences. Previous literature has proven that the work experiences of an internship program make a significant impact on students' career choices. Students who had undergone the internship program, particularly in the hospitality industry, agreed to some extent that previous internship satisfaction would have a strong influence on their career intentions. However, the essence of successful internship experiences lies in the satisfaction of students with their internships. Internship satisfaction is one area of research that has been largely neglected and little research has been done on it. Therefore, the purpose of this study is to identify the effect between job characteristics, organizational environment, and contextual factors with the internship satisfaction among hospitality undergraduates in Malaysian public universities. Besides, this study aims to determine the effect of internship satisfaction and self-perceived competence among hospitality undergraduates in Malaysian public universities. This study also aims to assess the most influential factors of internship satisfaction among job characteristics, organizational environment, and contextual factors. A quantitative research method was employed in this study, where it involved 302 hospitality undergraduates from eight public universities. The relationships among variables were analysed with Pearson Correlation analysis, multiple regression, linear regression and descriptive analysis. The models presented were evaluated with Partial Least Squares Structural Equation Modelling (PLS-SEM). Based on the findings from the PLS-SEM analysis, three independent variables (job characteristics, organizational environment, and contextual factors) had positively influenced internship satisfaction, so does internship satisfaction had positively influenced self-perceived competence. This study also found that organizational environment had the highest impact towards internship satisfaction (beta = 0.393), followed by job characteristics (beta = 0.301), and contextual factors (beta = 0.232). In conclusion, this study may extend the current literature on internship satisfaction and shed some light on related stakeholders, particularly universities, to strategize for a more effective internship program. This will enhance students’ internship satisfaction and later escalate their competencies for better emploment opportunities.